Cohesion and competitiveness of the European Union at strategic level - Eperjes, Zoltán (Acta Agraria Debreceniensis, 2013)
After the relaunchment of the Lisbon strategy, the cohesion policy of the EU concentrates even stronger on the establishment of the knowledge based economy, on R&D activities and innovations. In the first chapter I demonstrate the funds division of the convergence and regional competitiveness targets in the financial perspective between 2007–2013. The first sheet shows unambiguously that the new member states from Middle-Eastern Europe and the Mediterranean countries spend their funds on convergence and cohesion issues. The situation is contrary in the highly developed Western-European countries, in the core regions, where decisive part of the funds are spent on competitiveness issues. In the second chapter of the study I present the Europe 2020 strategy of the EU, that is a crucial paradigm change in the European strategy-making. While the Lisbon strategy focused on the social cohesion of the European Union, the Europe 2020 strategy strives the fostering of the European competitiveness. In the third part of the study I make a comparison how the funds-allocation altered during the two financial perspectives.